2021
DOI: 10.1002/joc.7033
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric impact of the boreal spring Pacific Meridional Mode on the following winter El Niño‐Southern Oscillation

Abstract: A number of previous studies have indicated that boreal spring Pacific Meridional Mode (SPMM) can exert notable impacts on the occurrence of El Niño-Southern Oscillation (ENSO) event during the subsequent winter. Here, we reveal that the impact of the SPMM on the following winter ENSO is asymmetric. During positive SPMM (+SPMM) years, strong westerly wind anomalies are induced over the tropical western Pacific via wind-evaporation-SST (WES) feedback. These westerly wind anomalies lead to pronounced sea surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 77 publications
(124 reference statements)
2
3
0
Order By: Relevance
“…Our study reconciles the seemingly contradictory viewpoints about the PMM asymmetry in previous studies (Fang and Yu (2020) suggested that −PMM > +PMM, but Zheng et al. (2021) and Fan et al. (2021) offered that +PMM > −PMM).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study reconciles the seemingly contradictory viewpoints about the PMM asymmetry in previous studies (Fang and Yu (2020) suggested that −PMM > +PMM, but Zheng et al. (2021) and Fan et al. (2021) offered that +PMM > −PMM).…”
Section: Discussionsupporting
confidence: 91%
“…Our study reconciles the seemingly contradictory viewpoints about the PMM asymmetry in previous studies (Fang and Yu (2020) suggested that −PMM > +PMM, but Zheng et al (2021) and Fan et al (2021) offered that +PMM > −PMM). Moreover, the present study declares the contribution of positively asymmetric stochastic PMM events to more frequent episodic El Niño events, which may provide an additional information in understanding the ENSO transition complexity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown that the prediction of ENSO evolution in both dynamical and statistical models can be improved when considering the NTA and SNP SST conditions 7 , 10 , 24 , 33 . Since 1980, all the cases of NTA warming (i.e., 1980, 1988, 1998, and 2010) were followed by a La Niña event 6 , and 7 out of the 15 cases of SNP warming (i.e., 1982, 1986, 1991, 1994, 1997, 2014, and 2014) were followed by an El Niño event 34 , 35 . Given that the impact of NTA and SNP SST on ENSO in enhanced under greenhouse warming, the northwestern hemispheric precursors are expected to contribute to increased forecast skill for ENSO.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has highlighted the differing capacities of warm and cold PMM phases in triggering ENSO (Fan et al., 2021; Thomas & Vimont, 2016; Zheng et al., 2021). These studies assessed PMM capabilities by examining SSTA intensity associated with subsequent ENSO induced by PMM.…”
Section: Introductionmentioning
confidence: 99%